2015
DOI: 10.1007/s13197-015-1711-9
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of iron in multiple fortified milk

Abstract: The objectives of the study were to evaluate the bioavailability of iron in milk fortified with ferric pyrophosphate (FPP) soluble and vitamin A acetate and to establish the role of vitamin A in enhancement of iron absorption. Balance indices viz. apparent digestibility coefficient, % retention/intake of iron and haematological parameters viz. blood haemoglobin, plasma ferritin, plasma transferrin and iron content in rat livers were analyzed to evaluate iron bioavailability. Anaemia was induced in one group of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…Similarly, higher %R/I in rats fed iron fortified diet as compared to sub‐group based on synthetic diet might be due to the presence of ascorbic acid which convert insoluble Fe 3+ to soluble Fe 2+ and improves the iron retention efficiency. Our results are in good agreement with the results of Sachdeva et al , who studied the %R/I in Wistar rat models and reported higher %R/I in animals fed iron + vitamin A fortified diets.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Similarly, higher %R/I in rats fed iron fortified diet as compared to sub‐group based on synthetic diet might be due to the presence of ascorbic acid which convert insoluble Fe 3+ to soluble Fe 2+ and improves the iron retention efficiency. Our results are in good agreement with the results of Sachdeva et al , who studied the %R/I in Wistar rat models and reported higher %R/I in animals fed iron + vitamin A fortified diets.…”
Section: Resultssupporting
confidence: 93%
“…It can be explained by the fact that on inducing diet‐based anaemia, the number of non‐haem iron absorption membrane receptors increases, and thus, enhances the iron absorption . Similar results have been reported by Pallares et al and Alferes et al Sachdeva et al investigated the iron bioavailability from fortified milk and observed significantly higher ADC in rats fed iron + vitamin A fortified diet than that of rats fed iron fortified diet and/or synthetic diet only in both normal as well as anaemic groups.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In this modern world, the demand of making novel foods is fulfilled by extrusion technology. Preservation and improvement of nutritional value of food during processing (Kaushik et al, 2017) has remained one of the most challenging tasks for researchers (Indumathi et al, 2015;Kaushik, Sachdeva, Arora, & Gupta, 2015;Sachdeva et al, 2015). To make a healthy extruded snack, it is important to wisely select multiple raw materials to achieve a balance between protein and carbohydrates.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary diversification, supplementation, and food fortification are widely accepted strategies to combat iron deficiency anemia. Food products successfully fortified with iron include milk, table salt, curry powder, sugar, fish sauce, dairy products, bakery products, maize flour and wheat flour (Sachdeva et al 2015;Muthayya et al 2012;Martinez-Navarrete et al 2002). Among the different food products fortified with iron, wheat flour fortification is a common practice worldwide.…”
Section: Introductionmentioning
confidence: 99%